Mewujudkan Kemandirian Desa Melalui Penguatan Inovasi Peternakan Itik dan Produk Turunannya Berbasis Ekonomi Sirkuler dan Berkelanjutan - Izwar Izwar; Jekki Irawan; Herri Darsan; Dazrullisa Dazrullisa; Dian Kristanti; Yusrizal Yusrizal (Universitas Teuku Umar, 2025)
Suak Sigadeng Village is administratively included in Johan Pahlawan District and has the determination to become a center for duck farming products in West Aceh Regency. Eggs, there are 2 community groups that carry out duck farming, namely the KWT Beu Jroh group of laying duck farms and the Baro Tabina Farmers Group of meat duck farms, in general both groups have understood the productive farming process, but there are several main problems in this dilution, namely dependence on factory feed, waste management, marketing management, processing of duck derivative products, so that strengthening of several of the above problems is needed, through training on making feed based on local ingredients, processing waste into fertilizer, financial management and marketing training. The training implementation method is carried out directly, actively and participatory, followed by practice by partner groups. The results show a positive effect for both groups in terms of training in terms of understanding, with an average score of 80, in addition to being followed by feed production reaching 300 kg / hour, and producing manure reaching 50 kg / 4 months. Overall, the KWT Beu Jroh group. After the treatment, there was a difference in the production of the KWT Beu jroh group from 150 salted eggs to 500 to 700 per day (depending on the availability of salted eggs), thus affecting the final income from Rp. 6,000,000 to Rp. 30,000,000 (minimum). Meanwhile, the comparison of the potential profit of the meat duck farming business of the Baro Tabina farmer group had a positive effect, including generating a difference in income from Rp. 12,800,000 to Rp. 22,800,000 in one maintenance cycle.